1996
DOI: 10.1515/ling.1996.34.5.1115
|View full text |Cite
|
Sign up to set email alerts
|

The aspect hypothesis and the emergence of tense distinctions in naturalistic L2 acquisition

Abstract: It is generally assumed that verbal inflections in early 12 acquisition primarily mark lexical aspect inherent in the verb or predicate with tense distinctions being neglected (=the aspect hypothesis). 1 This paper gives a brief account of the L2 acquisition of verbal inflections by two German children learning English without formal instruction. The results of the study are discussed in connection with the aspect hypothesis. They support the affiliation of verbal inflections with lexical aspect; however, cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 9 publications
(22 reference statements)
3
57
0
2
Order By: Relevance
“…A series of studies have reported similar findings on the acquisition of the English tense and aspect system by children (Rhode 1996;Gavruseva 2002) uninstructed adult learners in an ESL context (Robison 1990;Bardovi-Harlig and Bergström 1996), and instructed EFL and ESL learners (Bardovi-Harlig 1992;Robison 1995;Bardovi-Harlig and Reynolds 1995;Housen 2002;Collins 2002Collins , 2004Ayoun and Salaberry 2008).…”
Section: Evidence About the Acquisition Of The Progressive In Englishmentioning
confidence: 73%
See 4 more Smart Citations
“…A series of studies have reported similar findings on the acquisition of the English tense and aspect system by children (Rhode 1996;Gavruseva 2002) uninstructed adult learners in an ESL context (Robison 1990;Bardovi-Harlig and Bergström 1996), and instructed EFL and ESL learners (Bardovi-Harlig 1992;Robison 1995;Bardovi-Harlig and Reynolds 1995;Housen 2002;Collins 2002Collins , 2004Ayoun and Salaberry 2008).…”
Section: Evidence About the Acquisition Of The Progressive In Englishmentioning
confidence: 73%
“…Most studies in the area of the AH (Robison 1990;Bardovi-Harlig 1992;Huang 1993Huang , 1999Robison 1995;Shirai & Andersen 1995;Bardovi-Harlig & Reynolds 1995;Bardovi-Harlig & Bergström 1996;Rhode 1996Rhode , 2002Bardovi-Harlig 1998;Lee 2001;Housen 1995Housen , 2002Collins 2002Collins , 2004Gravuseva 2002;Clachar 2004;Ayoun & Salaberri 2008;Rhode 2009) have shown that verbal aspectual morphology is strongly associated with lexical aspect. By way of example, Robison (1990) carried out a study with 1 Spanish speaker learning English in the US.…”
Section: Evidence About the Acquisition Of The Progressive In Englishmentioning
confidence: 99%
See 3 more Smart Citations